If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -4(x + 30) = 24 Reorder the terms: x + -4(30 + x) = 24 x + (30 * -4 + x * -4) = 24 x + (-120 + -4x) = 24 Reorder the terms: -120 + x + -4x = 24 Combine like terms: x + -4x = -3x -120 + -3x = 24 Solving -120 + -3x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '120' to each side of the equation. -120 + 120 + -3x = 24 + 120 Combine like terms: -120 + 120 = 0 0 + -3x = 24 + 120 -3x = 24 + 120 Combine like terms: 24 + 120 = 144 -3x = 144 Divide each side by '-3'. x = -48 Simplifying x = -48
| 2n-10=x+20 | | 3(5x-2)+4(17-2x)-2(3x+1)=-1 | | 13x+17-4x=24 | | 19-2x-3=2x+3+x | | 2(x+1)=8(x-3)-10 | | 4y-3x-8=0 | | 8.3=4.1+10.5 | | 4y-6(y+4)=1-y | | 21a+21=28a+14 | | 5sinx-8cosx=6 | | 4(-5+x)=5x+.5 | | 2x^2+4x+4=20 | | .66666666666666(4x-5)=8 | | 18-(5m+8)=5+4m-13 | | 3x-5=7x+2-3 | | (4x-5)+(2x+20)=45 | | 6x+x-0.9=6x+0.9 | | -3-6X=28 | | X+65X+1000=0 | | (18)-2y-4= | | 3/4x+2-5/4=-6 | | 13=2f-5 | | 6x+3-8x-16=0 | | 5x+7=-7x+43 | | 9t=4 | | -2(3x+1)-10=4 | | 5x+3=33-x | | 1/4x+4=-6 | | 2-x=-2x-12 | | 3x+5=-x+13 | | 3[4-2(x-1)]=3x+3 | | 5x+6=2x+27 |